Site-directed mutagenesis of coumarin-type anticoagulant-sensitive VKORC1 - Rost, Simone; Fregin, Andreas; Hünerberg, Mirja; Bevans, Carville G.; Müller, Clemens R.; Oldenburg, Johannes (Thrombosis and Haemostasis, 2005)
Coumarin and homologous compounds are the most widely used anticoagulant drugs worldwide. They function as antagonists of vitamin K, an essential cofactor for the posttranslational γ-glutamyl carboxylation of the so-called vitamin K-dependent proteins. As vitamin K hydroquinone is converted to vitamin K epoxide (VKO) in every carboxylation step, the epoxide has to be recycled to the reduced form by the vitamin K epoxide reductase complex (VKOR). Recently, a single coumarin-sensitive protein of the putativeVKOR enzyme complex was identified in humans (vitamin K epoxide reductase complex subunit 1, VKORC1). Mutations inVKORC1 result in two different phenotypes: warfarin resistance (WR) and multiple coagulation factor deficiency type 2 (VKCFD2). Here, we report on the expression of site-directed VKORC1 mutants, addressing possible structural and functional roles of all seven cysteine residues (Cys16, Cys43, Cys51, Cys85, Cys96, Cys132, Cys135), the highly conserved residue Ser/Thr57, and Arg98, known to cause VKCFD2 in humans. Our results support the hypothesis that the C132-X-X-C135 motif inVKORC1 comprises part of the redox active site that catalyzes VKO reduction and also suggest a crucial role for the hydrophobicThr-Tyr-Ala motif in coumarin binding. Furthermore, our results support the concept that different structural components of VKORC1 define the binding sites for vitamin K epoxide and coumarin.
Keywords: Vitamin K; VKOR; warfarin; CXXC motif; mutagenesis